La industria audiovisual en andalucía y españa ante el surgimiento de nuevos clusters - Francisco Alberto Vallejo Peña (Cybergeo)
Companies clusters in the audio-visual sector have notoriously proliferated in recent times. This sector has an enormous dependency on the update of technology and infrastructure and, therefore, on the support of public boards, which are beginning to see in this sector a space that allows the economy to grow, added to the classic social and cultural interest that it has represented for the administration. After analyzing the main regional initiatives that have prospered in Spain in this scope (Galicia, Valencia and the Basque Country), in adition to the consolidated Madrid and Catalonia, we will approach the previous circumstances that face the Andalusian audio-visual sector and we will value its possibilities in terms of undertaking its own clusters. We will also evaluate the guidelines that have already been developped, presenting/displaying some recent data delivered by the administration, with the support of the vision of some experts of the sector.